PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEADILAN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Arimbawa, Putu Yoga; Dewi, A. A. Sagung Kartika (E-Jurnal Manajemen, 2019)
Organizational commitment is one of the important issues in the world of work. The purpose is to explain the effect of transformational leadership, organizational justice, and job satisfaction on organizational commitment. This research was conducted at Puri Saron Seminyak Hotel. Population is 109 people, in this study the method of determining the sample used using the formula slovin obtained results 52 people. Data collection is done through primary data in the form of questionnaires. The analysis technique used in this study uses multiple linear regression using independent variables of transformational leadership, organizational justice, and job satisfaction. Based on the results of this study, it can be concluded that transformational leadership has a positive and significant effect on the organizational commitment of Hotel Puri Saron Seminyak's employees. Organizational justice has a positive and significant effect on the organizational commitment of employees of Puri Saron Seminyak.